Transcranial direct current stimulation with Bosu-ball training increases cortical activation and improves ankle-foot function among individuals with chronic ankle instability: A randomized controlled trial - Xin Luo; Peixin Shen; Xueke Huang; He Gao; Yubin Ge; Zhiwen Dong; Yan Chen; Daniel T.P. Fong; Qipeng Song (PLoS ONE, 2026)
Objectives This study explored the effects of High-definition transcranial direct current stimulation (HD-tDCS) with Bosu-ball training on cortical activation and ankle-foot function among individuals with chronic ankle instability (CAI). Design Single-blind randomized sham-controlled trial. Setting Biomechanics laboratory. Methods Thirty-seven participants were allocated to tDCS+Bosu group (n=19) and Bosu group (n=18), received 6-week active or sham HD-tDCS with Bosu ball training. Change values of oxyhemoglobin concentration (ΔHbO 2 ) and Foot and Ankle Ability Measure (FAAM) were measured pre- and post-intervention. Two-way analysis of variance and Pearson correlation analysis were applied. Results We detected significant group-by-time interactions in ΔHbO 2 for the affected and non-affected side premotor cortex and supplementary motor area (PMC & SMA, channel 4: P=0.048; channel 14: P=0.047) and the affected side primary motor cortex (M1, channel 6: P=0.049), and significant time effects for the affected and non-affected side PMC & SMA (channel 2: P=0.043; channel 12: P=0.047), M1 (channel 5: P=0.041; channel 15: P=0.027; channel 16: P=0.049), primary somatosensory cortex (S1, channel 7: P=0.039; channel 17: P=0.043) and somatosensory association cortex (SAC, channel 8: P=0.021; channel 19: P=0.035). We detected significant interaction in the FAAM Sports subscale (P=0.046), and significant time effect in the FAAM Activities of Daily Living subscale (ADL subscale) (P<0.001). The increments in ΔHbO 2 of channels 4, 5, 16, 19 were moderately positively correlated with the increment in scores of the FAAM Sports subscale (P=0.015, P=0.006, P=0.008, P=0.003). The increment in ΔHbO 2 of channel 7 was weakly positively correlated with the increment in scores of the FAAM Sports (P=0.049) and ADL subscales (P=0.038). Conclusions Bosu-ball training increased cortical activation and improved ankle-foot function among individuals with CAI, and yielded more improvements with active HD-tDCS. The increment of cortical activation was positively correlated with the improvement of ankle-foot function.